(untitled) (Itinera, 2013)
The Neo-avantgardes of the 20th century left an indelible mark on the idea of theatre, establishing once and for all the concept of drama as a theatrical form, historically defined and based on identifiable criteria. The script as an end in itself was either dismissed – and pure performance was thus preferred –, or it was used as a device or starting point for what was occurring on stage in the hybrid, experimental theatrical forms. The role of playwrights – and therefore that of the script as an independently meaningful structure – fell into a deep crisis. By coming to grips with the new experiences, playwrights were able to explore new modes of textual expression, putting their art back on the right track. What dimensions do the categories of drama take on today? What are the new literary devices and techniques that contemporary playwrights can adopt? In order to try and answer these questions, we will analyse the script La demande d’emploi (The job application) by Michel Vinaver. Although written in 1971 – therefore, at the very beginning of the mentioned revolutionary period –, it already presents very important features of a type of playwriting that can be qualified as post-dramatic, like almost the entirety of the playwright’s work. We will explore and develop concepts like fragment, movement and polyphony, that can be frequently encountered in contemporary theatrical texts and with which both scholars and theatre professionals have to come to terms.